Scaffolding a conceptual support for personalized Arabic vocabulary learning using Augmented Reality (AR) enhanced flashcards - Zainuddin, Nurkhamimi; Sahrir, Muhammad Sabri; M. Idrus, Rozhan; Jaffar, Mohammad Najib (Universiti Kebangsaan Malaysia, 2016)
Technology Enhanced Learning (TEL) research has increasingly focused on emergent technologies such as Augmented Reality (AR), game and mobile to improve self-motivation and self-engagement of the learners in an appealing hybrid learning environment. This paper describes the development process of an augmented reality (AR) enhanced flashcards for non-native students of Universiti Sains Islam Malaysia (USIM) in scaffolding the memorization and retention of basic Arabic vocabulary through the inclusion of personalized learning using an application known as Aurasma. The study involved 24 elementary-level students in USIM and data collection was conducted by observing the students’ response and understanding in using the AR enhanced flashcards for personalized Arabic vocabulary learning. Findings indicated that the AR enhanced flashcards help in scaffolding the knowledge regarding the Arabic vocabulary learning. Furthermore, the findings showed that the AR enhanced flashcards facilitate the process of Arabic vocabulary personalized learning. The study showed that the augmented reality could be considered as one of the personalized learning platform that can be used to help students in memorizing certain information and maintained their knowledge of Arabic vocabulary, and creating novel sentences by using the target vocabularies more than half of the time.